Development of Vertical Cavity Surface Emitting Laser Modulation for Data Communication. (October 2020) - Cao, Yixin
Abstract: This paper includes some basic knowledge of VCSEL and reviews some researches focusing on development of modulation characteristics in data communication of 850nm, 980nm, 1060nm and 1100nm VCSEL, which is helpful to researchers who are studying in this field. The popular modulation in data communication VCSEL is also mentioned in this paper. There are still some difficulties in the modulation of VCSEL-based links directly, which may be solved by modulating relaxation-oscillation frequency of VCSEL in the near future.